Religions in progress or regress: inner strength matters, from the buddhist perspective - Poey, Tiang Peow (Council for Innovative research (CIR), 2013)
Religions in general offer remedies to aching minds and therefore humans seek relief for their problems in life. Spirituality is always a matter of concern and people who follow different religions are constantly searching for it. Man becomes helpless in extreme difficulties and it is quite natural that religions play significant roles in human lives. It is mainly because the complexities in life are being increased day by day and to encounter this people take refuge in spirituality. All religions offer some sort of solutions and so they are relevant among the followers. Therefore, they play decisive roles in the life of individuals. Religions are not only sets of beliefs, but they also provide guidelines to the people’s life. They become ideals of people, strengthening their inner values and morals in life. But increased institutionalization of religions and some of the practices and customs may distract people from them. Involvement of religions in politics in certain areas in the globe has also created a negative attitude among the common people. Communal tensions, terrorism, atrocities and even war are caused because of the differences of the opinions among followers of different religions. There might be strong reasons why people are deviated from religions and the practices. In order to address those issues, Buddhism as a philosophy answers the basic problems of life, as it explains the causes of conflicts and the needs for the enlightenment. In this paper, I attempt to show how the inner strength of individuals can be a very crucial aspect that can help man to achieve wisdom in all aspect, and in so doing we argue that new outcome and religious education would be necessary to help the society as well as the individuals to that end. This paper also argues that the development of mutual understanding and a peaceful survival of mankind necessitate religious education and interaction between various ideologies.